A preliminary study on multi-level biomarkers response of the tropical oyster Crassostrea brasiliana to exposure to the antifouling biocide DCOIT. (January 2022) - Campos, Bruno Galvão de; Fontes, Mayana Karoline; Gusso-Choueri, Paloma Kachel; Marinsek, Gabriela Pustiglione; Nobre, Caio Rodrigues; Moreno, Beatriz Barbosa; Abreu, Fiamma Eugenia Lemos; Fillmann, Gilberto; de Britto Mari, Renata; Abessa, Denis Moledo de Souza
Abstract: This study investigated the sublethal effects of environmentally relevant concentrations of DCOIT on the neotropical oyster Crassostrea brasiliana . Gills and digestive glands of animals exposed to increasing concentrations of DCOIT were analyzed for biochemical, cellular, and histopathological responses. Exposure to DCOIT (0.2 to 151 μg L −1 ) for 120 h triggered oxidative stress in both tissues (through the modulation of GPX, GST, GSH and GR), which led to damage of membrane lipids (increase of LPO and reduction of the NRRT). DCOIT increased histopathological pathologies in gills, such as necrosis, lymphocyte infiltration and epithelial desquamation. This study showed that short term exposure to environmental concentrations of DCOIT causes negative effects on C. brasiliana at biochemical, physiological, and histological levels. Therefore, the use of DCOIT as a booster biocide in antifouling paints should be further assessed, as it may cause environmental hazards to marine organisms. Graphical abstract: Unlabelled Image Highlights: DCOIT caused biochemical, cellular, and histopathological effects on C. brasiliana Digestive gland and gills presented tissue-specific responses at biochemical level Modulation of antioxidant enzymes led to oxidative stress and lipid peroxidation DCOIT damaged lysosomal membranes and increases histopathological pathologies Environmental concentrations of DCOIT are enough to affect C. brasiliana